2018
DOI: 10.1155/2018/6190859
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transfusion Practice among Healthcare Personnel in Nepal: An Observational Study

Abstract: Background The complications associated with errors in transfusion practice can be minimized by assessing transfusion practices. In Nepal, there is no standard protocol on blood transfusion. So, this study was conducted with an aim to assess the blood transfusion practice among healthcare personnel. Methods A descriptive observational study was conducted in two tertiary hospitals in Kathmandu, Nepal, over a period of 10 months. Bedside blood transfusion procedures were observed using structured checklist. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
1
11
0
3
Order By: Relevance
“…al. [ 10 ] and 33.9% by Sapkota et al [ 21 ] from Nepal. Majority (60.70%) of the participants in the present study knew that blood must be returned to blood bank within 30 min if not transfused unlike what was observed by Hijji et al [ 10 ] where 50.0% nurses would transfuse the blood kept in the room temperature even beyond 90 min after delivery to the ward.…”
Section: Discussionmentioning
confidence: 99%
“…al. [ 10 ] and 33.9% by Sapkota et al [ 21 ] from Nepal. Majority (60.70%) of the participants in the present study knew that blood must be returned to blood bank within 30 min if not transfused unlike what was observed by Hijji et al [ 10 ] where 50.0% nurses would transfuse the blood kept in the room temperature even beyond 90 min after delivery to the ward.…”
Section: Discussionmentioning
confidence: 99%
“…Blood transfusion has a wellestablished clinical effect in the treatment of anaemia, where it improves oxygen delivery to tissues. (Sapkota et al, 2018). The issues connected with transfusion errors can be reduced by monitoring transfusion processes.…”
Section: Introductionmentioning
confidence: 99%
“…The issues connected with transfusion errors can be reduced by monitoring transfusion processes. Standard guidelines or rules addressing important procedures of blood transfusion management, such as screening donor blood for infectious diseases, establishing the necessity for transfusion, and determining ABO compatibility, are utilized in many countries (Sapkota et al 2018). The majority of transfusion errors are caused by human factors, which can be avoided with proper training and transfusion procedure updates (Dasaraju & Subraya 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A previous observational prospective study similarly found that 72% of the participants did not obtain informed consent from the patients and family before initiating blood transfusion [ 17 ]. Another observational study of two tertiary hospitals in Nepal also found that 2.4%–8.2% of 86 observations of blood transfusions done involved informing patients and family of reasons for transfusion, benefits, and potential risks whilst seeking informed consent to transfuse [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This sharply contrasts with findings from an observational study in Nepal in which only 2–4% carried out assessment of vital signs within the first 15 minutes of initiating blood transfusion. The difference may be on account of the methodological differences between the studies as knowledge has been shown not to be translated into practice on many occasions [ 18 ].…”
Section: Discussionmentioning
confidence: 99%